RELASI TINGKAT KEHARMONISAN KELUARGA DENGAN KONSEP DIRI REMAJA - Asvi Isminayah; , Supandi (al-Balagh : Jurnal Dakwah dan Komunikasi, 2016)
Self concept is individual evaluation of ones characteristics and ability. A family as the first and major institution for the adolescent has an important role in providing education, love, guidance and supervision so they can grow up with positive self concept. The purpose of the research is to know the relationship between the harmony level of family and the self concept of adolescent in Bayat, Klaten. The research uses correlative quantitative method. It involves 53 adolescent chosen by random sampling. The result of the research shows high harmony level of family in Bayat (71,7%), and high category of adolescents self concept (56,6%). The hypothesis testing with Pearson Product Moment correlative analysis shows that there is positive and significant relationship between the harmony level of family and the adolescents self concept with the probability 0,000 (< 0,05) and correlation coefficient (rxy) 0,713.